Spowiedź dziecięcia wieku - Brzezińska, Martyna (Czytanie Literatury. Łódzkie Studia Literaturoznawcze, 2012)
The essay “Confession of a Child of the Century” attempts to diagnose the act of reading in time of the new media. The author does not try to figure out the answer but investigates the influence of technology on the reading process. Shall we consider it as a possible thread to literature? Is the death of the book always negative in all aspects, or is it a new way to develop readership among people? Finally, maybe the dislike of new technology is just ignorance, maybe the discussion of both sides overdue and pointless? The essay is meant to provide a youth’s perspective on current reading trends, so it is not difficult to guess which side of discussion author defends.